\(x^2-\sqrt{x^2-5}=7\)
\(\Leftrightarrow\sqrt{x^2-5}=x^2-7\)
\(\Leftrightarrow\left(\sqrt{x^2-5}\right)^2=\left(x^2-7\right)^2\)
\(\Leftrightarrow x^2-5=\left(x^2\right)^2-2.x^2.7+7^2\)
\(\Leftrightarrow x^2-5=x^4-14x^2+49\)
\(\Leftrightarrow-x^4+x^2+14x^2-5-49=0\)
\(\Leftrightarrow-x^4+15x^2-54=0\)
Đặt : \(t=x^2\left(t\ge0\right)\) , ta có :
\(-t^2+15t-54=0\)
\(\left(a=-1;b=15;c=-54\right)\)
\(\Delta=b^2-4ac\)
\(=15^2-4.\left(-1\right).\left(-54\right)\)
\(=225+4.\left(-54\right)\)
\(=225-216\)
\(=9>0\)
\(\sqrt{\Delta}=\sqrt{9}=3\)
\(t_1=\frac{-15+3}{2.\left(-1\right)}=6\) ( nhận )
\(t_2=\frac{-15-3}{2.\left(-1\right)}=9\) ( nhận )
Vs : \(t_1=6\Rightarrow x^2=6\Rightarrow x=\pm\sqrt{6}\)
Vs : \(t_2=9\Rightarrow x^2=9\Rightarrow x=\pm3\)
Vậy phương trình có 4 nghiệm : \(x_1=3;x_2=-3;x_3=6;x_4=-6\)
Cái đề có gì đó sai sai
\(\)